TXT Rx: using health information technology to safely discharge suicidal patients from the ED. (1st March 2011) - Larkin, G L; Beautrais, A L; Meredith, T; Tabakakis, K
Abstract : Background: Increasingly, postsuicide attempt patients are discharged after emergency department (ED) and mental health evaluation, only to recidivate in the weeks to months after discharge. Study objectives: To evaluate the feasibility, acceptability and cost-effectiveness of using an automated SMS text messaging programme to engage patients with outpatient services versus repeated ED care. Methods: A mixed methods study of general ED patients at risk of suicidal ideation or attempt. Design: A retrospective cohort quasi-experimental design assessing rates of suicide attempt and ED attendance pre- and postintervention. Postintervention, semi-structured interviews with a selected subsample of patients assessed feasibility, acceptability and satisfaction with SMS text messaging. The intervention employed Ecological Momentary Assessment to monitor mood and tailor automated SMS message response. Setting: General ED (annual volume 77 000 visits). Participants: Randomly selected adult (>16 years) ED patients. Results: Of 1112 patients screened, 5.6% (N=62) had silent suicidal ideation or planning, revealed only on ED screening. Compared to 12 months prior to the intervention, patients allocated to the TXT Rx programme were less likely to return to the ED for any reason (25% vs 8%). None of the patients receiving the intervention made a suicide attempt in the first 6 months after discharge. In follow-up semi-structured interviews, patients receiving the SMS Rx intervention reported high rates of feasibility (98%), acceptability (95%) and satisfaction with the programme (95%). Conclusion: ED patients with suicidal ideation or planning may be safely discharged with tailored, SMS text message follow-up.